THE CHANGING AND DECLINE OF JOHOR KANGKAR SETTLEMENTS: A CASE STUDY OF MUAR, JOHOR - Low Hui Ching; Raja Nafida Raja Shahminan; Fadhlina Ahmad@Taufik (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Kangkar is a traditional Chinese historic settlement in Johor, which established during Kangchu system from 1844 to 1917 represents strong historical significance in the Chinese architectural paradigm. However, the number of kangkar settlements decrease drastically from 100-120 to less than 20 in current context. This article aims to identify the possible reasons of kangkar decline in order to give insight in developing conservation policy for the historic settlement. Historical method was employed through archival research, literature review, and historical cartography; while field trip was carried out to examine the current development of kangkars. The findings revealed that 75% of kangkars are lost while the rest of 25% have been survived at least partly in today’s context. The establishment of New Village Resettlement and development of new town near to the kangkar settlements greatly contributed to the diminishing of kangkars at Muar. In short, the identification of reasons contributes to decline of kangkars act as the lessons to be integrated in traditional village conservation or town development planning in the future. This could avoid further neglect, gradual deterioration, and destruction of the traditional environment built with the experiences gained over the centuries.